2385. Ceftazidime–Avibactam in Combination With Fosfomycin: A Novel Therapeutic Strategy Against Multidrug-Resistant Pseudomonas aeruginosa. (26th November 2018) - Papp-Wallace, Krisztina M; Zeiser, Elise T; Becka, Scott A; Park, Steven T; Winkler, Marisa L; Nguyen, Kevin; Singh, Indresh; Sutton, Granger; Fouts, Derrick E; Ellis-Grosse, Evelyn J; Drusano, George L; Perlin, David S; et al.
Abstract: Background: By targeting penicillin binding protein-3, the AmpC β-lactamase, and MurA, another enzyme involved in cell wall synthesis, with the ceftazidime–avibactam–fosfomycin combination, we previously overcame multidrug resistance (MDR) in vitro in an archived collection of Pseudomonas aeruginosa clinical isolates. Here, we further validate the ceftazidime–avibactam–fosfomycin combination using the MDR P . aeruginosa clinical isolate, CL232. Methods: Whole genome and transcriptome sequencing, checkerboard analysis, and determination of mutation frequency as well as mutation prevention concentration were conducted. In addition, the ceftazidime–avibactam–fosfomycin combination was tested in a neutropenic thigh murine infection model with a high bacterial burden (2 × 10 7 colony forming units (CFUs)) of MDR P . aeruginosa clinical isolate CL232. Results: Checkerboard analysis revealed slight synergy with fractional inhibitory concentration index of 0.53 for 25–6.25 μg/mL of ceftazidime–avibactam combined with 12.5 μg/mL of fosfomycin. Accordingly, the resistance elements in P . aeruginosa CL232 were analyzed via whole-genome sequencing (WGS) and transcriptome sequencing (RNAseq). WGS of CL232 revealed mutations in genes (e.g., oprD, ampR ) that contribute to β-lactam resistance. Moreover, expression of the AmpC β-lactamase and the MexAB-OprM efflux pump were upregulated (~2–6-fold). The potential for the development of ceftazidime–avibactam-fosfomycin resistance was assessed in vitro . Fosfomycin alone was found to have a high mutation frequency 1.9 × 10 −5 ; however, the addition of ceftazidime–avibactam reduced this frequency by 3-logs. In addition, the ceftazidime–avibactam–fosfomycin combination possessed the lowest mutation prevention concentration at 64 mg/L–4 mg/L–64 mg/L. In a neutropenic thigh murine infection model, the ceftazidime–avibactam–fosfomycin combination was found to reduce CFUs by 5–6 logs compared with vehicle-treated mice, while ceftazidime–avibactam and fosfomycin dosed separately decreased CFUs by ~1 log and 2–3 logs, respectively. Conclusion: The combination of ceftazidime–avibactam–fosfomycin is highly likely to offer patients who suffer from infections with a high bacteria burdens (i.e., pneumonia) a therapeutic hope against MDR P . aeruginosa . Disclosures: K. M. Papp-Wallace, F. Hoffmann-La Roche Ltd: Grant Investigator, Research grant. E. J. Ellis-Grosse, Zavante Therapeutics, Inc., : Employee and Shareholder, Salary.